Trepidation among the “keepers”: Gendered Perceptions of Fear and Risk of Victimization among Corrections Officers - Gordon, Jill A. (American journal of criminal justice, 2013)
Determining the attitudes of correctional officers relative to their level of fear and risk of victimization is important to investigate due to the relationship of the conditions of confinement and the care and custody of offenders. Furthermore, consideration of such attitudes by gender may uncover differences because of the unique obstacles female corrections officers face. This study examines the level of fear and risk of both inmate and staff related victimization by gender through administering a survey to all corrections officers employed in the adult prisons within one-state. The overall analysis indicated some level of apprehension among officers regarding their fear and risk of victimization for inmate-precipitated victimization more than staff-to-staff victimization. Female officers were also more likely to demonstrate a higher level of perceived fear and risk of inmate-precipitated and staff-precipitated victimization. In addition, race and security level were shown to be significant as predictors of both fear and perceived risk of victimization among officers.